2016
DOI: 10.1177/2372732216685333
|View full text |Cite
|
Sign up to set email alerts
|

Treating Chronic Stress to Address the Growing Problem of Depression and Anxiety

Abstract: Treating chronic stress via biofeedback and mindfulness may reduce the rising disease burden of depression and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 54 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…The current study conducted interventions for each participant over 10-12 weeks. A significant decrease in stress scores could be linked to the duration of the program, as previous research by Steffen et al has shown that physiological changes may occur within three weeks [ 17 ]. Ratanasiripong et al conducted a biofeedback intervention targeting stress reduction in public health students, yielding similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The current study conducted interventions for each participant over 10-12 weeks. A significant decrease in stress scores could be linked to the duration of the program, as previous research by Steffen et al has shown that physiological changes may occur within three weeks [ 17 ]. Ratanasiripong et al conducted a biofeedback intervention targeting stress reduction in public health students, yielding similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to Cash & Whittingham (2010), aspects of mindfulness including the nonjudgmental aspect and the present moment experience aspect are helpful in contributing to the treatment of anxiety. Other strengths of mindfulness include its preventative nature (Steffen & DeBarros, 2017) and use as a self-management strategy (Khusid & Vythilingam, 2016). Additionally, mindfulness is relatively cheaper to administer and the treatment can be delivered in a variety of ways, including face to face and remotely on the web (Farris et al, 2021).…”
Section: Introductionmentioning
confidence: 99%